3D Electrohydrodynamic Printing of Contact Lens‐Like Chloramphenicol‐Loaded Patches for Corneal Abrasions Treatment. Issue 2 (22nd November 2022) - Sun, Renyuan; Wang, Baolin; Li, Xinyue; Chang, Ming-Wei; Yan, Xinghao; Zhang, Longfei
Abstract : Corneal abrasion is a common traumatic emergency, which can cause eyelid photophobia, tearing, and obvious foreign body sensation and pain. Herein, the 3D contact lens‐like chloramphenicol‐loaded patches composed of well‐organized micrometer fibers are prepared via electrohydrodynamic (EHD) printing to treat corneal abrasions. The main material of these patches is cellulose acetate (CA), and chloramphenicol (CAM) is loaded in the patches. EHD printing can realize micrometer fibers stacked layer by layer to form a customizable shape suitable for eye wear. Herein, the surface morphology, chemical as well as physical properties, transparency, drug release behaviors, and biocompatibility of the patches loading various concentrations of CAM are studied. It is found that the CAM‐loaded patches have 3D hemispherical shape similar to contact lens and smooth surface morphology. Moreover, patches loaded with different concentrations of CAM all maintain good water absorption, hydrophilicity, light transmittance, and biocompatibility. The drug release curves of CAM‐loaded patches show that the contact lens‐like patches have high loading efficiency and can achieve sustained release of CAM, indicating clinical potential in the treatment of corneal abrasions. Abstract : The 3D contact lens‐like chloramphenicol‐loaded patches composed of well‐organized micrometer fibers are prepared via electrohydrodynamic (EHD) printing.  The micrometer fibers are stacked layer by layer, forming a customizable shape suitable for eye wear. Meanwhile, this patch shows high light transmittance, indicating its great potential to be applied for corneal abrasions in the future.